Assessing compliance: Active versus inactive trainees in a memory intervention - Dana K Bagwell (Dove Medical Press, 2008)
Dana K Bagwell, Robin L WestDepartment of Psychology, University of Florida, Gainesville, FL, USAAbstract: Extensive research on memory interventions has confirmed their success with older adults, but the individual difference factors that predict successful training outcomes remain relatively unexplored. In the current intervention, trainees were identified as active (compliant with training regimens) or inactive using trainer ratings based on attendance, homework completion, and class participation. The active group showed significantly greater training-related gains than the inactive group and the control group on most measures. Compliance was predicted by health, education, and self-efficacy. Specifically, active trainees were more likely to have advanced degrees and somewhat higher self-efficacy, and to have higher vitality and fewer functional limitations than the inactive trainees. This research may assist future investigators to target interventions to those who will show the most benefit.Keywords: compliance, memory training, aging, intervention